A critical analysis of student teachers’ intervention in language education: A Study based on Diploma students’ action research reports - Gabriel, Bazimaziki (International Journal of Scientific Research and Management (IJSRM), 2017)
Contemporary studies in education prove action research to hold an important part in Higher Learning Institutions in particular. No one could undermine the role that action research plays in education where participants learn by identifying a problem and do something to try to solve it. In this study, the researcher critically analyzes Diploma students’ intervention in language education during teaching practice often times carried out as one of the requirements for the completion of their studies. Convenient sampling was used to choose action reports of students from the combinations related to languages education. Selected action research reports were conducted by five different groups who carried their internship in various parts of the country. These corpora were analyzed basing on the aim of the study. Discussion and analysis was framed on Susman’ Action Research Model. It has been found that all the five groups had good action research topics which could help them improve learners’ language proficiency. They identified well research problems concerning English language teaching and learning. However, they failed to show clearly what they did to help learners improve English language proficiency yet it should be their primary contribution to solving the existing problem they had stated themselves. It was recommended that interns would leave school for internship well prepared and equipped with enough knowledge and skills about action research so that they can grapple with the problem they can identify there